Acute effect of different stretching methods on Illinois Agility Test in soccer players - Amiri-Khorasani, M.; Sahebozamani, M.; Tabrizi, K. G.; Yusof, A. B. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to examine the effects of static, dynamic, and the combination of static and dynamic stretching within a pre-exercise warm-up on the Illinois agility test (IAT) in soccer players. Nineteen professional soccer players (age = 22.5 ± 2.5 years, height = 1.79 ± 0.003 m, body mass = 74.8 ± 10.9 kg) were tested for agility performance using the IAT after different warm-up protocols consisting of static, dynamic, combined stretching, and no stretching. The players were subgrouped into less and more experienced players (5.12 ± 0.83 and 8.18 ± 1.16 years, respectively). There were significant decreases in agility time after no stretching, among no stretching vs. static stretching; after dynamic stretching, among static vs. dynamic stretching; and after dynamic stretching, among dynamic vs. combined stretching during warm-ups for the agility: mean ± SD data were 14.18 ± 0.66 seconds (no stretch), 14.90 ± 0.38 seconds (static), 13.95 ± 0.32 seconds (dynamic), and 14.50 ± 0.35 seconds (combined). There was significant difference between less and more experienced players after no stretching and dynamic stretching. There was significant decrease in agility time following dynamic stretching vs. static stretching in both less and more experienced players. Static stretching does not appear to be detrimental to agility performance when combined with dynamic warm-up for professional soccer players. However, dynamic stretching during the warm-up was most effective as preparation for agility performance. The data from this study suggest that more experienced players demonstrate better agility skills due to years of training and playing soccer.